Gibberellic acid induces unique molecular responses in ‘thompson seedless’ grapes as revealed by non-targeted metabolomics - Jadhav, Uma; Mundhe, Swapnil; Kumar, Yashwant; Jogaiah, Satisha; Upadhyay, Anuradha; Gupta, Vidya S.; Kadoo, Narendra Y. (Journal of Plant Growth Regulation, 2021)
Compact clusters and small berry size are the major problems associated with the commercialization of table grapes. The application of gibberellic acid 3 (GA3) has been a long-followed practice to overcome these issues. To analyze the molecular response of ‘Thompson Seedless’ grapes to GA3 treatment, we investigated the metabolomes of its rachises, clusters, and berries, 6 h and 24 h after the treatment. Metabolite profiling using non-targeted metabolomics approach revealed several metabolites, including arginine, proline, tyrosine, kaempferol, resveratrol, catechin, and so on as possible biomarkers of GA3 treatment in grapes. GA3 treatment greatly impacted the alanine, aspartate, and glutamate metabolism pathways, and the GA3-mediated alterations in the levels of certain plant growth regulators and primary metabolites were in accordance with important growth and developmental processes in grapes. This study highlights the effect of GA3 on the profiles of certain polyphenols impacting the flavone and flavonol biosynthesis pathways and hence the nutritional aspect of grapes. The results of this study would be useful to develop self-elongating varieties simplifying the grape cultivation.

Gibberellic acid induces unique molecular responses in `thompson seedless' grapes as revealed by non-targeted metabolomics - Jadhav, Uma; Mundhe, Swapnil; Kumar, Yashwant; Jogaiah, Satisha; Upadhyay, Anuradha; Gupta, Vidya S.; Kadoo, Narendra Y. (Journal of Plant Growth Regulation, 2021)
Compact clusters and small berry size are the major problems associated with the commercialization of table grapes. The application of gibberellic acid 3 (GA(3)) has been a long-followed practice to overcome these issues. To analyze the molecular response of `Thompson Seedless' grapes to GA(3) treatment, we investigated the metabolomes of its rachises, clusters, and berries, 6 h and 24 h after the treatment. Metabolite profiling using non-targeted metabolomics approach revealed several metabolites, including arginine, proline, tyrosine, kaempferol, resveratrol, catechin, and so on as possible biomarkers of GA(3) treatment in grapes. GA(3) treatment greatly impacted the alanine, aspartate, and glutamate metabolism pathways, and the GA(3)-mediated alterations in the levels of certain plant growth regulators and primary metabolites were in accordance with important growth and developmental processes in grapes. This study highlights the effect of GA(3) on the profiles of certain polyphenols impacting the flavone and flavonol biosynthesis pathways and hence the nutritional aspect of grapes. The results of this study would be useful to develop self-elongating varieties simplifying the grape cultivation.
Keywords: Biosynthetic pathways; GA(3) response; GA(3) signaling; Sultana grapes; Untargeted metabolomics